Dentro da câmara de eco: os mecanismos sociais por trás da troca de informações distorcidas - Queiroz, Bruna Scoralick (2025)
The circulation of information plays a central role in shaping opinions and structuring public debate. In the digital environment, algorithmic personalization has intensified informational fragmentation, fostering the emergence of echo chambers—spaces where beliefs are reinforced, and divergent narratives are systematically discredited. These structures impact individuals, the informational environment, and society, contributing to polarization, institutional distrust, and radicalization. This study investigates how information distortion occurs within the anti vaccine echo chamber, analyzing the internal dynamics that sustain participant engagement and their resistance to external information. A qualitative approach was adopted, combining netnography and in-depth interviews with members of these groups. Data analysis followed the method of Gioia et al. (2013), allowing for the construction of an interpretative model of the internal functioning of the anti-vaccine echo chamber. Beyond the informational perspective, this study incorporates gift theory to understand how the circulation of narratives in these spaces operates as a form of symbolic exchange that strengthens collective identity and group belonging. The findings advance the understanding of echo chambers by demonstrating that their maintenance relies not only on the central role of distortion but also on social dynamics that encourage individuals to remain within these spaces. These conclusions contribute to the academic literature on echo chambers by offering a model that explains their functioning.